2019
DOI: 10.4236/ce.2019.105073
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Language Games on Smartphones in Developing Arabic Speaking Skills among Non-Native Speakers

Abstract: This study investigates the impact of using smartphones to develop Arabic speaking skills among Arabic non-native speakers through a language game. The experiment was conducted by introducing the independent variable (language game on smartphone) on the study sample of 15 University of Sydney students learning Arabic at the beginner level. The experiment was conducted throughout semester 2/2015. Students spent 24 hours of self-study using the language game via smartphones. They were subjected to a pre-and a po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 12 publications
(11 reference statements)
0
9
0
Order By: Relevance
“…All six studies focused on game-based Arabic language learning, but the target group and research design of the studies were different depending on the nature. They followed pre-test/post-test design (i.e., 3/15) (Kotob and Ibrahim, 2019;Ritonga et al, 2022;Abdelhamid et al, 2023), quantitative approach (i.e., 8/15) (Sahrir and Alias, 2011;Yan Mei et al, 2018;Azmi and Zakaria, 2020;Putri et al, 2021;Riwanda et al, 2021;Bin Jaafar and Yusoff, 2022;Ismath et al, 2022;Noor et al, 2023), content analysis (i.e., 1/15) (Al-Bulushi and Al-Issa, 2017), experiment (i.e., 3/15) (Kenali et al, 2019;Al Hejaili and Newbury, 2023;Mazer and Al-Ajlouni, 2023), and qualitative approach (i.e., 1/15) (Ghani et al, 2019). The details of the research design are also shown in Figure 3.…”
Section: Focus Aim and Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…All six studies focused on game-based Arabic language learning, but the target group and research design of the studies were different depending on the nature. They followed pre-test/post-test design (i.e., 3/15) (Kotob and Ibrahim, 2019;Ritonga et al, 2022;Abdelhamid et al, 2023), quantitative approach (i.e., 8/15) (Sahrir and Alias, 2011;Yan Mei et al, 2018;Azmi and Zakaria, 2020;Putri et al, 2021;Riwanda et al, 2021;Bin Jaafar and Yusoff, 2022;Ismath et al, 2022;Noor et al, 2023), content analysis (i.e., 1/15) (Al-Bulushi and Al-Issa, 2017), experiment (i.e., 3/15) (Kenali et al, 2019;Al Hejaili and Newbury, 2023;Mazer and Al-Ajlouni, 2023), and qualitative approach (i.e., 1/15) (Ghani et al, 2019). The details of the research design are also shown in Figure 3.…”
Section: Focus Aim and Approachmentioning
confidence: 99%
“…Two out of 15 focused on learners' behaviors and attitudes toward online games for learning the Arabic language (Sahrir and Alias, 2011;Kotob and Ibrahim, 2019). Others focused on learning via mobile games through quizzes (Ghani et al, 2019;Kenali et al, 2019;Ismath et al, 2022;Mazer and Al-Ajlouni, 2023), classroom games (Al-Bulushi and Al-Issa, 2017; Azmi and Zakaria, 2020;Riwanda et al, 2021;Ritonga et al, 2022;Noor et al, 2023), and online games (Yan Mei et al, 2018;Putri et al, 2021;Bin Jaafar and Yusoff, 2022;Ritonga et al, 2022).…”
Section: Focus Aim and Approachmentioning
confidence: 99%
“…The mobile digital game is an effective tool that has good potential in helping digital native in learning purposes (Noor Azli et al, 2019). It has been recognised as an excellent learning tool to motivate students to participate in teaching and learning activities actively as well as develop positive perception and attitude (Alessi & Trollip, 1984;Amna et al, 2017;Azman et al, 2018;Baid & Lambert, 2010;Chu & Hung, 2015;Hamadallah et al, 2019;Hamizul & Nik Mohd Rahimi, 2015;Han & Gwo, 2013;Insorio, 2021;Kirikkaya et al, 2010;Li & Tsai, 2013;Muhammad Sabri, 2011;Siti Nazleen & Zuliana, 2017;Wilfried et al, 2014). It could improve student's knowledge, develop enjoyment in the class environment, engage students throughout the learning process, and develop soft skills such as leadership and decision making (Hwang et al, 2012;Insorio, 2021;Lee & Hammer, 2011;Muhideen et al, 2021;Najdi & Sheikh, 2012;Paiva et al, 2016;Sung & Hwang, 2013;Papastergiou, 2009;Yien et al, 2011).…”
Section: / 18mentioning
confidence: 99%
“…(2) Flipped learning provides students with interactive language learning environment Language communication and interaction is the crucial purpose of language learning [17] and writing involves "an interaction between three elements that interact in getting to the final product: 1) the text, 2) the writer, 3) the reader" [18] . Flipped learning "frees instructional time, consequently allowing for more dynamic and interactive classroom" [19] where students could first interact with the text before class [20] and teachers as readers of the writing performance, could have more time to respond to students' writing and provide feedback in class [17] .…”
Section: The Feasibility and Reasons For Flipped L2 Classesmentioning
confidence: 99%
“…Since engagement is closely related with effectiveness of learning [31] , when they are more engaged, students are more likely to acquire different skills and improve their knowledge acquisition [17] . In terms of second language acquisition, Brown also states that the learner engagement is key to the FL/L2 learning [32] .…”
Section: Gamification Engagement and Language Learningmentioning
confidence: 99%